Histopathological Analysis and Comparison between Experimentally Fabricated Hydroxyapatite from Nile Tilapia Bone and Mineral Trioxide Aggregate as A Direct Pulp Capping Agents on Dog Pulp (In Vivo Study) - Essa, Mona; Tohamy, Safaa (Open Access Macedonian Journal of Medical Sciences, 2022)
AIM: The aim of this study was to study response of exposed dental dog pulp to the HP from Nile Tilapia bone and MTA on induction of reparative dentin formation and to inflammatory response in pulp tissue. MATERIALS AND METHODS: Four male mongrel dogs 1 year old with total of 20 teeth from each dog were selected and divided into two groups that each group has 40 teeth according to the material used as pulp capping agents. The maxillary teeth and the mandibular teeth for each dog were capped by both materials alternatively; the cavities were then sealed by glass-ionomer cement. Each group divided in two groups according to 2-time intervals (4 weeks and 8 weeks). Animals were sacrificed and teeth were collected for histopathological analysis. RESULTS: Specimens capped by fish bone powder after 4 weeks, which showed non-significantly higher of inflammatory cell scores than that capped by MTA. It showed thin (score 1) to moderate (score 2) thickness of dentine bridge formation, mostly a-tubular dentin, in all specimens. After 8 weeks, significant decrease in inflammatory cell infiltration scores for both groups were found, but it was significant in case of fish bone powder. Furthermore, dentine bridge became more significant for both materials with slight histological change in the group capped by fish bone powder. CONCLUSIONS: HA from Nile Tilapia bone could be considered as a direct pulp capping material. Furthermore, more studies needed on the fabrication of this material to give better result in shape and the pattern of reparative dentine formed.